2020
DOI: 10.1016/j.corsci.2020.108953
|View full text |Cite
|
Sign up to set email alerts
|

Intergranular corrosion: Comparison between experiments and cellular automata

Abstract: In this paper, a 3D cellular automata approach of intergranular corrosion in presented. A model is proposed, along with experimental results both qualitatively (groove morphology, groove angle distribution) and quantitatively (mass loss, corrosion rate, corrosion front evolution). Simulations have been performed using a new asynchronous algorithm: the choice of the most adequate grid is also discussed. The model investigates the statistical variation of the corrosion front and provides useful information to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…For this last one, as it was difficult to extract information from experiments, we used CA modeling. Indeed, we showed that CA is able to reproduce accurately the experimental behavior [33,47].…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…For this last one, as it was difficult to extract information from experiments, we used CA modeling. Indeed, we showed that CA is able to reproduce accurately the experimental behavior [33,47].…”
Section: Introductionmentioning
confidence: 84%
“…These probabilities drive the evolution of the system from a time t to the following time t + Δt, according to transition rules: a IGN (or GRN) cell that is contact with a SOL cell has a probability Pgrn (or Pign) to convert into a SOL cell. The way to fix the values of Pign and Pgrn so as to reproduce adequately the experimental results (with CA to experiments conversion factors) is described in reference [33].…”
Section: We Performed Corrosion Tests (Electrochemical Measurements A...mentioning
confidence: 99%
See 3 more Smart Citations